2019
DOI: 10.1002/jsfa.9826
|View full text |Cite
|
Sign up to set email alerts
|

Production of selenium‐biofortified microgreens from selenium‐enriched seeds of basil

Abstract: BACKGROUND: Microgreens (i.e. tender immature greens) are a popular alternative to sprouts (i.e. germinating seeds) because of their higher content of vitamins, carotenoids and phenols, as well as their lower content of nitrates. Their nutritional value can be improved by biofortification, which increases micronutrient levels during plant growth. Because selenium (Se) plays a significant role in antioxidant defense, biofortification with Se is a good way of improving the nutritional quality of sprouts and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
8
38
1
1
Order By: Relevance
“…No deleterious effect of Se treatments was observed on the fresh yield of the four microgreen genotypes studied. The non-significant effect on yield observed in green and purple basil was in agreement with previous studies on Se-biofortified microgreens [9] and mature plants [26] of basil. On the other hand, the beneficial Se effect found on the yield of coriander and tatsoi was consistent with the growth-promoting response to low Se doses demonstrated in previous works on rice sprouts [49] and mature plants of Indian mustard [50], ryegrass [51], spinach [52], and lettuce [53].…”
Section: Fresh Biomass Yield and Dry Matter Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…No deleterious effect of Se treatments was observed on the fresh yield of the four microgreen genotypes studied. The non-significant effect on yield observed in green and purple basil was in agreement with previous studies on Se-biofortified microgreens [9] and mature plants [26] of basil. On the other hand, the beneficial Se effect found on the yield of coriander and tatsoi was consistent with the growth-promoting response to low Se doses demonstrated in previous works on rice sprouts [49] and mature plants of Indian mustard [50], ryegrass [51], spinach [52], and lettuce [53].…”
Section: Fresh Biomass Yield and Dry Matter Contentsupporting
confidence: 92%
“…The nutraceutical value of microgreens may be further enhanced through biofortification with micronutrients. Selenium (Se) applications have been shown to have the dual effect of both enriching food with an essential microelement and increasing the overall content of bioactive compounds in microgreens [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for patients with impaired kidney function requiring a low potassium diet, the nutrient solution used can be prepared with low or no potassium (Renna, Castellino, Leoni, Paradiso, & Santamaria, ). Puccinelli, Malorgio, Rosellini, and Pezzarossa () found that selenium supplementation of the hydroponic nutrient solution for basil microgreens produced selenium‐enriched leaves and increased antioxidant capacity. Since rocket microgreens accumulate nitrogen excessively, the ability to meet E.U.…”
Section: Other Nutritional Facetsmentioning
confidence: 99%
“…Proportional enhancement of the Se content in plants after adding its various concentrations to the soil was described earlier by other authors. 12,29,30 Translocation of Se between organs was observed by Germ et al 31 and Turakainen et al 32 after its foliar application in potato. In potato plants, Se preferentially accumulated in the leaves, roots, and stolons rather than in tubers.…”
Section: Resultsmentioning
confidence: 93%